2018
DOI: 10.1177/0363546517748906
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Graft Size Is Significantly Associated With Increased Force and Decreased Chondrocyte Viability

Abstract: Based on the current data, graft depth is an important consideration for surgeons when sizing osteochondral allograft transplant for chondral lesions of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The ideal depth of the allograft should be limited to 6 to 10 mm depending on the size and location of the graft. 91 0.00 100.00…”
Section: 86mentioning
confidence: 99%
See 2 more Smart Citations
“…The ideal depth of the allograft should be limited to 6 to 10 mm depending on the size and location of the graft. 91 0.00 100.00…”
Section: 86mentioning
confidence: 99%
“…In this regard, higher impact loads may be encountered when the graft is thicker than 10 mm and when there is a >2-mm difference between the graft and recipient hole, and thus, thinner plugs are now recommended that match the depth of the socket. 71,91 Laboratory studies demonstrated that high-impact loads adversely affect cell viability, with less than 50% to 70% of the cells remaining viable in that setting. 71,91 The load of impact has a larger influence on chondrocyte death than the number of impacts.…”
Section: Graft and Surgical Technique Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer grafts were found to require an increased number of insertional impacts and cumulative impact force detrimental to surface chondrocyte viability and graft survival. [12][13][14] Studies exist evaluating the biomechanical properties of OCAs of 7 mm in depth and longer, but no study has clearly defined the minimal graft depth required to resist deforming forces. [15][16][17] Deforming forces leading to graft protrusion or subsidence of more than 1 mm can lead to unfavorable outcomes and fibrocartilaginous, rather than osteochondral incorporation.…”
mentioning
confidence: 99%
“…1,4,16 The utilization of shallower grafts, still capable of resisting deforming forces, may allow for less host autoimmune response, less surface chondral damage secondary to insertion forces, and less recipient site morbidity. 4,11,12 In addition, pulsatile lavage (PL) of OCAs is commonly performed to minimize residual antigenic factors in an attempt to decrease immunogenic material as well as increase volume for host osseous integration. 1,4 Allograft empty marrow volume was found to increase from 36 to 55% after fresh OCAs were subjected to 45 to 120 second periods of PL.…”
mentioning
confidence: 99%